IMF Research Bulletin, December 2010. (IMF Research Bulletin; IMF Research Bulletin, 2010)
The Q and A in this issue features seven questions about emerging markets and the financial crisis (by Ayhan Kose); the research summaries are "Tax Revenue Response to the Business Cycle" (by Cemile Sancak, Ricardo Velloso, and Jing Xing) and "Banking Crisis Resolution: Was this Time Different?" (by Luc Laeven and Fabian Valencia). The issue also lists the contents of the second issue of the IMF Economic Review, Volume 58 Number 2; visiting scholars at the IMF during October-December 2010; and recent IMF Working Papers and Staff Position Notes.